The Importance of Applying Organic Fertilizers to Food Grape Varieties - O.O.Sattorov; Sh.E.Yursunova (Global Scientific Publishing, 2022)
The positive effect of the combined use of organic and mineral fertilizers on the yield and quality of grapes can be seen in the colorful varieties of table grapes. Because it takes time, they are planted in the vineyards in late autumn and early spring. Currently, manure, which is one of the organic fertilizers, is also applied during the vegetation period.
Keywords: Bio humus; organic matter; colorful table grapes; liquid preparation